Proactive and Reactive Attitude to Crisis: Evidence from European Firms - Jan Brzozowski; Marco Cucculelli (Entrepreneurial Business and Economics Review)
Objective: The aim of this study is to investigate the behaviour of European firms in the time of the economic crisis in 2008-2009. We analyse the determinants of proactive strategies in the context of innovation and the range of products offered by every firm on the market.